Achromatic temporal-frequency responses of human lateral geniculate nucleus and primary visual cortex. (October 2016) - Bayram, Ali; Karahan, Esin; Bilgiç, Başar; Ademoglu, Ahmet; Demiralp, Tamer
Graphical abstract: Highlights: Early visual BOLD responses depend on the temporal frequency of the stimuli. LGN response displays relatively flat frequency characteristics compared with V1. V1 response peaking around 10 Hz shows strong low-pass characteristics above 14 Hz. Low-pass effect possibly stems from the circuitry of V1 or extra-striate cortex. Similar LGN and V1 BOLD fluctuations suggest thalamo-cortical oscillatory tuning. Abstract: The sensitivity of the sensory systems to temporal changes of the environment constitutes one of the critical issues in perception. In the present study, we investigated the human early visual system's dependency on the temporal frequency of visual input using fMRI. Blood oxygen level-dependent (BOLD) responses of the lateral geniculate nucleus (LGN) and primary visual cortex (V1) were investigated in a wide frequency range (6–46 Hz) with fine frequency sampling (13 frequencies). Subject-specific functional-anatomic ROIs were derived from the combination of the anatomic template masks and the functional maps derived from multi-session fMRI analyses across all 13 stimulation conditions. Using functional-anatomic ROIs, average responses of LGN and V1 were calculated for each frequency. The V1 surface area was further parsed into 7 eccentricity sectors to detail central and peripheral responses. LGN's response revealed fluctuations on a background of non-significant decrease of the BOLD response with increasing stimulation frequency, while V1 response displayed similar fluctuations with a global maximum in the range of 8–12 Hz, but a rapid and significant decrease with increasing stimulation frequency especially above 14 Hz. This behavior of V1 response valid for both central and peripheral vision emphasizes that the profound low-pass effect of the visual system to visual input emerges in V1, presumably generated by the intra-cortical circuitry of V1 or projections from extra-striate areas. Besides, the high correlation between LGN and V1 BOLD responses across all visual stimulation frequencies supports the oscillatory tuning in thalamo-cortical interactions as previously claimed in electrophysiological studies.